2021
DOI: 10.1097/opx.0000000000001854
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Axial Eye Growth on Foveal Avascular Zone Measurements in Children

Abstract: SIGNIFICANCE Foveal avascular zone (FAZ) area is a frequently used biomarker in diseases impacting the retinal vasculature in pediatric populations. Variation in axial length between individuals results in differences in lateral image scale, which affect the accuracy of FAZ area measurements. Accordingly, changes in axial length over time within individual children would affect estimates of FAZ area change. PURPOSE This study aimed to quantify how changes in axial lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…The PAROS method could be extended to these types of imaging modalities, but doing so would require further validation to ensure accurate mathematical description of the camera. Interestingly, various OCT studies report a similar variation (up to 25% 41 , 42 ) of image scaling as found in this study ( Fig. 6 A), suggesting a similar clinically relevant impact of correcting for magnification differences.…”
Section: Discussionsupporting
confidence: 87%
“…The PAROS method could be extended to these types of imaging modalities, but doing so would require further validation to ensure accurate mathematical description of the camera. Interestingly, various OCT studies report a similar variation (up to 25% 41 , 42 ) of image scaling as found in this study ( Fig. 6 A), suggesting a similar clinically relevant impact of correcting for magnification differences.…”
Section: Discussionsupporting
confidence: 87%
“…22 , 28 , 29 A recent paper showed a reversal of correlation between foveal avascular zone and aging in children by correction for axial length in this context. 47 However, the lateral distortion in our images should have led to fewer (positive or negative) curvature measures in longer eyes and vice versa in shorter eyes and should not have changed the direction of the curvature. It therefore should not alter the main conclusions of our analysis.…”
Section: Discussionmentioning
confidence: 87%